Exploring the role of trifarotene against RAR-α: an investigation of expression pattern and clinicopathological significance of RAR-α in breast cancer - Jan, Nusrat; Sofi, Shazia; Abo Mansoor, Adel; Abdelrahim, Adil; Ahmad, Irshad; Almilabairy, Abdullah; Ahmad, Fuzail; Mir, Manzoor Ahmad (Frontiers in Pharmacology, 2024)
The members retinoic acid receptors (RARs) (α, β, and γ) and retinoid X receptors (RXRs) (α, β, and γ) belong to the retinoid receptor family. They regulate the biological action of classical retinoids through nuclear retinoid receptors, a transcription factor that is regulated by ligands. Through the binding of particular retinoic acid-responsive elements (RAREs) located in target gene promoters, RARs and members of the RXRs form heterodimers. By binding to its nuclear receptors and triggering the transcription of the target genes downstream, retinoic acid (RA) mediates the expression of certain genes. RARs are essential for many biological processes, such as development, immunity, reproduction, organogenesis, and homeostasis. RARs are also linked to pathologies and tumors due to mutations, protein fusions, changes in expression levels, or abnormal posttranslational changes that lead to aberrant functions and homeostasis breakdown. The oncogenic development of animal tissues or cultured cells is linked to altered expression of retinoid receptors. The RAR-α is over-expressed in several malignancies. Increased invasion and migration in several cancer forms, including HNSC carcinoma, pediatric low-grade gliomas, lung adenocarcinoma, and breast cancer, have been linked to its upregulated expression. Numerous approved therapeutic regimens targeting RAR-α have been developed, improving patient survival rates. Objective: This study's main objective was to identify novel RAR-α-targeting drugs and evaluate the expression patterns of RAR-α in breast cancer patients.In-silico investigation using a variety of bioinformatics tools like UALCAN, TISCH, TIMER 2.0, ENRICHR, and others were employed to examine the expression of RARα. Further, we evaluated the RAR-α expression and inhibition in breast cancer through in-vitro analysis. Results: Our research indicates that RAR-α is upregulated in several malignancies including Breast Cancer. It regulates granulocyte differentiation and has an association with the retinoic acid receptor signaling pathway and cellular response to estrogen stimulus. Furthermore, trifarotene was found as a potential synthetic compound that targets RAR-α through in-silico and in-vitro study. Conclusion: Overall, this research indicates that elevated expression of RAR-α enhances the onset of breast cancer. Using trifarotene medication to target RAR-α will significantly boost the response of breast cancer individuals to treatment and delay the development of resistance to drugs.